METACOGNITIVE STRATEGIES: INVESTIGATING EFL STUDENTS' SELF-EVALUATION OF SPEAKING PERFORMANCE DURING ONLINE LEARNING - Ryantika Dyah Safitri; Lilia Indriani (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2020)
This study examines an investigation toward EFL students' self-evaluation in speaking performance to report the metacognitive strategies using during an online class. The participants were 35 EFL students at the English Department of a state university. Self-evaluation is a type of metacognitive strategy in which students assess and measure their work (Amanda Arp, 2016). This study is based on previous research regarding self-evaluation by Amanda Arp in 2016. Researcher using the coding self-evaluation that was adapted from thirty self-evaluations based on the use of descriptive coding (SaldaÃ±a). A questionnaire was administered to the EFL students to explore their self-evaluation strategy towards their speaking performance during online classes. The results show that there are almost all participants applied the Metacognitive strategy which is self-evaluation toward their speaking performance during an online class